Analisis Kepatuhan Penggunaan Dana Desa yang Efektif dan Efisien di Desa Seso Kecamatan Jepon Kabupaten Blora - ristina; Reikha Habibah Yusfi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the quality of planning and competency of village officials in managing Village Funds, using a case study in Seso Village, Jepon District, Blora Regency. Village Funds are a strategic instrument for strengthening village independence, supporting infrastructure development, and increasing participation and accountability in village financial management, as mandated by Law Number 6 of 2014 and Minister of Finance Regulation Number 145 of 2023. The research approach used was descriptive qualitative, with data collection through semi-structured interviews with eight informants, consisting of village heads and village officials directly involved in Village Fund planning and management. The study indicates that the Village Funds in Seso Village have been planned with community involvement and in accordance with applicable regulations. Although several technical obstacles remain in document preparation and understanding evolving regulations. The competence of village officials is considered adequate in carrying out administrative and financial tasks, further technical training and direct mentoring are still needed, particularly in the use of the SISKEUDES application, preparing budgets (RAB), and financial reporting. This study recommends sustainable capacity building for village officials to support more transparent, accountable, and targeted Village Fund governance.